2020
DOI: 10.1186/s43088-020-00058-8
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of pharmacological properties of Argentine stingless bee geopropolis

Abstract: Background: Propolis is a natural product that has been widely utilized as medicine and dietary supplement because of its broad biological activities. However, although meliponide hive products have many advantages, meliponiculture has not yet become popular in Argentina, and few scientific studies on its chemical composition and/or its bioactive properties were reported, so the use of stingless bee propolis Argentine in popular medicine continues to be based on empirical knowledge. Our work aims to evaluate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 25 publications
(34 reference statements)
1
14
0
Order By: Relevance
“…The research was conducted on rats given propolis extracts, which also effectively suppress the cough brought on by ammonia. Furthermore, there was no evidence of acute toxicity at dosages ranging from 2,000 to 5,000 mg/kg of body weight [ 54 56 ]. This highlighted that propolis from M. subnitida is one of the major potential products to be utilized in future treatments.…”
Section: The Biological Potential Of Propolis From Stingless Bees In ...mentioning
confidence: 99%
“…The research was conducted on rats given propolis extracts, which also effectively suppress the cough brought on by ammonia. Furthermore, there was no evidence of acute toxicity at dosages ranging from 2,000 to 5,000 mg/kg of body weight [ 54 56 ]. This highlighted that propolis from M. subnitida is one of the major potential products to be utilized in future treatments.…”
Section: The Biological Potential Of Propolis From Stingless Bees In ...mentioning
confidence: 99%
“…[15] Currently, products derived from species of the genus Scaptotrigona are an unexplored source of potential therapeutic compounds, despite evidence that some of them are widely used in traditional medicine and have several records in the literature that confirm their bioactivities. [18][19][20] Furthermore, in the literature, there is still no comprehensive review of the bioactivities and chemical composition associated with species of this genus of stingless bees.…”
Section: Introductionmentioning
confidence: 99%
“…The health-promoting capabilities of propolis depend mainly on the constituent of phenolic compounds and their composition. In the last decade, studies have investigated the biological activities of propolis, a variety found in Argentina, Iranian, Morocco, Indonesia, Chinese, and Malaysia (Isla et al, 2001;Mohammadzadeh et al, 2007;Mountassir et al, 2014;Sabir & Sumidarti, 2017;Sun et al, 2018;Nna et al, 2018Nna et al, , 2021Fikri et al, 2019;Brodkiewicz et al, 2020). Studies have attributed some jms.mabjournal.com Muhamad Suhaini et al, 2023 Malaysian Applied Biology pharmacological properties to the complex phenolic compounds in propolis.…”
Section: Introductionmentioning
confidence: 99%
“…Since propolis is used as a natural nutraceutical for various human health conditions, its biosafety must be ascertained through acute toxicity testing. Recently, an acute toxicity test performed by Brodkiewicz et al (2020) reported that oral administration of ethanol extracts of propolis at 2000 mg/kg and 5000 mg/kg doses did not cause any adverse effects and consider a safe amount for a short period of 48 hr and a prolonged period of 14 days.…”
Section: Introductionmentioning
confidence: 99%